Optimum problem of piezoelectric laminated composite plate using genetic algorithm - Ngoc, Le Kim; Thinh, Tran Ich (Vietnam Journal of Mechanics, 2009)
The finite element model based on First Shear Displacement Theory to study the mechanical and electrical behaviors of cantilever laminated composite plate bonded piezoelectric patches on surface is presented. A nine-node isoparametric rectangular element with 5 degrees of freedom for the generalized displacements and 2 electrical degrees of freedom at each node is used. Optimization techniques based on genetic algorithm (GAs) are applied in order to maximize the piezoelectric actuator efficiency, improve the structural performance. The illustrative examples and results of the appropriate applied voltages, position of bonded piezoelectric actuator patches and fiber angle to achieve the desired displacement of the cantilever composite plate are presented